Properties of charcoal produced from reaction wood in trees inclined due to wind - Boschetti, Walter Torezani Neto; Pereira, Matheus Perdigão de Castro Freitas; Soratto, Deborah Nava; Boa, Ana Carolina; Carneiro, Angélica de Cássia Oliveira; Vidaurre, Graziela Baptista; Carvalho, Ana Márcia Macedo Ladeira (Revista Árvore, 2017)
Inclined trees produce reaction wood, whose properties are distinct from normal wood. This situation can affect the production of charcoal. This study was conducted to evaluate the quality of charcoal derived from reaction wood in trees of a commercial plantation inclined due to the action of wind. We used six year old wood from a Eucalyptus grandis xEucalyptus urophylla hybrid from plantations located in Minas Gerais. The physical and chemical properties of the wood were determined as well as the gravimetric yield and charcoal properties. According to the results, there were significant differences between the properties of the reaction and normal wood, with the reaction wood having lower levels of lignin and extractives, greater holocellulose content and low specific gravity. However, these characteristics of reaction wood did not significantly affect the properties of its charcoal.

Árvores inclinadas produzem madeira de reação, cujas propriedades são distintas da madeira normal e, podem afetar na produção de carvão vegetal. Este trabalho foi realizado com objetivo de avaliar a qualidade do carvão vegetal procedente da madeira de reação em árvores de plantio comercial inclinadas por ação de ventos. Utilizou-se madeira de um híbrido de Eucalyptus grandis x Eucalyptus urophylla aos seis anos de idade proveniente de plantios localizados em Minas Gerais. Determinaram-se as propriedades físicas e químicas da madeira, e também o rendimento gravimétrico e as propriedades do carvão vegetal. De acordo com os resultados, houve diferenças significativas entre as propriedades da madeira de reação e normal, tendo a madeira de reação menores teores de lignina e extrativos, maior teor de holocelulose e menor densidade básica. No entanto, essas diferenças na madeira de reação não afetaram significativamente as propriedades do carvão vegetal.
Keywords: Carbonization; Reaction wood; Wood properties